a)
\(5x^2+9y^2-12xy-6x+9=0\)
\(\Leftrightarrow\left(4x^2-12xy+9y^2\right)+\left(x^2-6x+9\right)=0\)
\(\Leftrightarrow\left(2x-3y\right)^2+\left(x-3\right)^2=0\)
Vì \(\hept{\begin{cases}\left(2x-3y\right)^2\ge0\\\left(x-3\right)^2\ge0\end{cases}}\)nên
\(\Rightarrow\hept{\begin{cases}\left(2x-3y\right)^2=0\\\left(x-3\right)^2=0\end{cases}\Rightarrow\hept{\begin{cases}2x-3y=0\\x-3=0\end{cases}\Rightarrow}\hept{\begin{cases}x=3\\y=2\end{cases}}}\)
Vậy x=3 và y=2
b)
\(2x^2+2y^2+2xy-10x-8y+41=0\)
\(\Leftrightarrow\left(x^2+2xy+y^2\right)+\left(x^2-10x+25\right)+\left(y^2-8y+16\right)=0\)
\(\Leftrightarrow\left(x+y\right)^2+\left(x-5\right)^2+\left(y-4\right)^2=0\)\(\)
Vì \(\hept{\begin{cases}\left(x+y\right)^2\ge0\\\left(x-5\right)^2\ge0\\\left(y-4\right)^2\ge0\end{cases}}\)nên
\(\Rightarrow\hept{\begin{cases}\left(x+y\right)^2=0\\\left(x-5\right)^2=0\\\left(y-4\right)^2=0\end{cases}\Rightarrow\hept{\begin{cases}x+y=0\\x-5=0\\y-4=0\end{cases}\Rightarrow}\hept{\begin{cases}x+y=0\\x=5\\y=4\end{cases}}}\)( VÔ nghiệm vì \(x+y\ne0\))
Vậy không có giá trị x, y nào thỏa mãn đề bài